PENGARUH MAKROEKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN - Yediza Govindo Simarmata; Namira Ufrida Rahmi; Yulisfan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of the Indonesian capital market has experienced increasingly dynamic changes along with global economic integration and macroeconomic uncertainty. The Indonesia Composite Index (ICI) serves as an important indicator in reflecting the performance of the Indonesian stock market. During the 2024–2026 period, the Indonesian capital market faced various challenges caused by global interest rate pressures, exchange rate fluctuations, and changes in world economic conditions. Therefore, this study aims to analyze the influence of macroeconomic variables on the Indonesia Composite Index in Indonesia. The variables examined include inflation, rupiah exchange rate, interest rates, Gross Domestic Product (GDP), and world oil prices. This study employed a quantitative approach to examine the relationships among variables and test the proposed hypotheses. The population consisted of macroeconomic and Indonesia Composite Index data from 2021 to 2025, with all population data used as the sample through a saturated sampling technique. Data analysis was conducted using statistical methods to identify the influence of each macroeconomic variable on the Indonesia Composite Index. The results indicate that interest rates, Gross Domestic Product (GDP), and world oil prices significantly influence the Indonesia Composite Index. Meanwhile, inflation and the rupiah exchange rate do not show a significant effect on the Indonesia Composite Index. The adjusted R-square value of 0.691 demonstrates that 69.1% of the variation in the Indonesia Composite Index can be explained by the independent variables. These findings suggest that macroeconomic conditions play an important role in influencing investment decisions and stock market movements in Indonesia.